Male circumcision wound healing in human immunodeficiency virus (HIV)‐negative and HIV‐positive men in Rakai, Uganda. (27th November 2013) - Kigozi, Godfrey; Musoke, Richard; Kighoma, Nehemiah; Watya, Stephen; Serwadda, David; Nalugoda, Fred; Kiwanuka, Noah; Nkale, James; Wabwire‐Mangen, Fred; Makumbi, Frederick; Sewankambo, Nelson K.; Gray, Ronald H.; et al.
Abstract : Objective: To assess completed wound healing after medical male circumcision (MMC) among human immunodeficiency virus (HIV)‐negative and HIV‐positive men with cluster of differentiation 4 (CD4) counts of <350 and ≥350 cells/mm 3, as minimal data are available on the safety of MMC among HIV‐positive men with low CD4 counts. Patients and Methods: In all, 262 HIV‐negative and 177 HIV‐positive consenting males aged ≥12 years accepted MMC using the dorsal slit procedure and were enrolled in the study. Socio‐demographic and behavioural data and blood for HIV testing and CD4 counts were collected at baseline. Participants were followed weekly to collect information on resumption of sex, condom use and both self‐reported and clinically assessed wound healing. The proportions healed among HIV‐positive men were compared with HIV‐negative men. Time to complete wound healing was assessed by Kaplan–Meier survival analysis. Results: There were no statistically significant differences in the proportion of men healed by HIV status. At 4 weeks, the proportions healed were 85.9% in HIV‐negative men, 77.4% in HIV‐positive men with a CD4 count of ≥350 cells/mm 3 and 87.1% in HIV‐positive men with a CD4 count of <350 cells/mm 3 . The median time to healing was 4 weeks and did not vary by HIV or CD4 status. All men had certified complete wound healing at 6 weeks after MMC. In all, 1.4% of HIV‐positive men with a CD4 count of <350 cells/mm 3 resumed sex before healing, compared with 8.5% among HIV‐positive men with a CD4 count of ≥350 cells/mm 3 ( P = 0.052) and 7.8% ( P = 0.081) among HIV‐negative men. Conclusion: Inclusion of HIV‐positive men with low CD4 counts in MMC services is not deleterious to postoperative wound healing.